Brentuximab Vedotin Plus AVD for First-Line Treatment of Early-Stage Unfavorable Hodgkin Lymphoma (BREACH): A Multicenter, Open-Label, Randomized, Phase II Trial. Issue 2 (22nd July 2022) - Fornecker, Luc-Matthieu; Lazarovici, Julien; Aurer, Igor; Casasnovas, René-Olivier; Gac, Anne-Claire; Bonnet, Christophe; Bouabdallah, Krimo; Feugier, Pierre; Specht, Lena; Molina, Lysiane; Touati, Mohamed; Borel, Cécile; et al.
Abstract : PURPOSE: The prognosis of patients with early-stage unfavorable Hodgkin lymphoma remains unsatisfactory. We assessed the efficacy and safety of brentuximab vedotin plus doxorubicin, vinblastine, and dacarbazine (BV-AVD) in previously untreated, early-stage unfavorable Hodgkin lymphoma (ClinicalTrials.gov identifier: NCT02292979 ). METHODS: BREACH is a multicenter, randomized, open-label, phase II trial. Eligible patients were age 18-60 years with ≥ 1 unfavorable EORTC/LYSA criterion. Patients were randomly assigned (2:1) to four cycles of BV-AVD or standard doxorubicin, bleomycin, vincristine, and dacarbazine (ABVD), followed by 30 Gy involved node radiotherapy. The primary end point was the positron emission tomography (PET) response rate after two cycles by expert independent review using the Deauville score. The study was designed to test if the PET-negative rate after two cycles of BV-AVD was superior to 75%. We hypothesized a 10% increase in the PET-negative rate after two cycles of BV-AVD. RESULTS: Between March 2015 and October 2016, 170 patients were enrolled. After two cycles, the primary end point of the study was met: 93 (82.3%; 90% CI, 75.3 to 88.0) of 113 patients in the BV-AVD arm were PET-negative (Deauville score 1-3) compared with 43 (75.4%; 90% CI, 64.3% to 84.5%) of 57 in the ABVD arm. The 2-year progression-free survival (PFS) was 97.3% (95% CI, 91.9 to 99.1) and 92.6% (95% CI, 81.4% to 97.2%) in the BV-AVD and ABVD arms, respectively. High total metabolic tumor volume was associated with a significantly shorter PFS (hazard ratio, 17.9; 95% CI, 2.2 to 145.5; P < .001). For patients with high total metabolic tumor volume, the 2-year PFS rate was 90.9% (95% CI, 74.4 to 97.0) and 70.7% (95% CI, 39.4% to 87.9%) in the BV-AVD and ABVD arms, respectively. CONCLUSION: BV-AVD demonstrated an improvement in the PET-negative rate compared with ABVD after two cycles.